Researching milieu-specific perceptions of risk, (in)security, and vulnerability. A conceptual approach for understanding the inequality and segregation nexus in urban spaces. - Seidelsohn, Kristina; Voss, Martin; Krüger, Daniela (Springer, 2018)
Die Autoren und Autorinnen gehen davon aus, dass die Fähigkeit der Stadtbewohner, sich nach einer großen Katastrophe zu schützen oder ihre Normalität wiederherzustellen, ungleich verteilt ist. Sie beschreiben einen Ansatz zur Beurteilung milieuspezifischer Wahrnehmungen von Risiko, Unsicherheit und Verwundbarkeit und argumentieren, dass Ansätze zur Vermittlung von Risikoprävention und zur Umsetzung nachhaltiger Anpassungsstrategien nicht erfolgreich sein können, wenn nicht die subjektiven Wahrnehmungsmuster der Stadtbewohner einbezogen werden.

European cities are characterized by a growing social inequality, residential segregation as well as socio-cultural differentiation. Consequently, the capability of urban residents to protect themselves or to resume normality after a large-scale disaster is unequally distributed. In this chapter, we develop and exemplify a conceptual approach to assess milieu-specific perceptions of risk, (in)security, and vulnerability and further this research within the conceptual frame-work of sociological disaster research. We argue that approaches to communicate risk prevention, to implement sustainable adaptation strategies, or to reduce unequally distributed vulnerabilities cannot be successful without the engagement of the inhabitant's subjective perception patterns. A milieu-oriented research approach allows for the linking of the subjective dimension of risk, vulnerability, and (in)security with the social and spatial distribution of resources and capital (Bourdieu, in: Die feinen Unterschiede) which both form and reproduce social and spatial segregation (Scheffer and Voss, in: Erfolg durch Schlüsselqualifikationen? "Heimliche Lehrpläne" und Basiskompetenzen im Zeichen der Globalisierung. Pabst Science Publishers, Berlin 2008). Using a case study in a mid-sized German City as a basis, we will sketch the theoretical approach first, then exemplify it with empirical results, and close by drawing some conclusions an milieu-specific perceptions of risks, (in)security, and vulnerability in urban spaces.
Keywords: Stadtbewohner; Sozialgruppe; Soziale Ungleichheit; Risikobewertung; Unsicherheit; Vulnerabilität; Wahrnehmung; Klimaanpassung; Risikovorsorge; Informationsvermittlung